The Failure of a Rural Development Project: South Korean Official Development Assistance in the Democratic Republic of the Congo - Lim, Hyung Baek; Kim , Chulwoo (Asian Journal of Agriculture and Rural Development, 2020)
The purpose of this study is to investigate failure factors of the official development assistance provided by South Korea for an integrated rural development project located in the village of Kitshini in the Democratic Republic of the Congo (DRC). Regional studies on the DRC were carried out on a macro level, and on the Kitshini project on a micro-level was done through literature review and participant observations. The findings indicate five inevitable exogenous variables that greatly reduced the project’s efficiency, first, tribalism and tribal conflict, second, incomplete administrative organization at the local level, third, shortage of agricultural technology and agricultural market openings, four, unrealistic goals for the project, and five, the tragedy of the commons. The results suggest the necessity to conduct comprehensive research on the local area and preliminary feasibility studies to secure sufficient time to plan the project and design suitable initiatives for recipient countries and target sites.